ملف التعريف للمفردات اللغوية في العربية لغة ثانية: دراسة تقويمية في المدارس الثانوية بولاية قدح، ماليزيا - Nurulhuda Abu Bakar (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study represents productive vocabulary created by Form Five students in several schools in Kedah, Malaysia. This study consists of four chapters, begins with the research plan. The main focus is to identify the total number of vocabulary created in essays in three examinations, along with the type of vocabulary such as the nouns, verbs and preposition.When a person talks about vocabulary, it is undeniable to put aside the language skills since they are connected to each other such as the writing, the speaking, the listening and the reading skills. The researcher states the importance of productive vocabulary in learning the second language together with the meaning of productive vocabulary. This research also indicates the linguistic distance of the Arabic as a second language in this study. Besides, the researcher also discusses the relationship between gender and productive vocabulary. This is because the result shows that there is no difference in production of total vocabulary and its types between both male and female students. The researcher also discusses the possibilities in how the male and the female students were brought up could be a big issue in producing vocabulary and its types whereas the results do not show any difference between both of them. The researcher also provides a quick introduction to the secondary schools in Malaysia and list down strategies used in learning vocabulary in schools. In the third chapter, the researcher has also stated the process in asking permission from the government departments before starting her study along with supported documents before analyze and discuss the result in the forth chapter.